2015
DOI: 10.1242/dev.118927
|View full text |Cite
|
Sign up to set email alerts
|

ATRX contributes to epigenetic asymmetry and silencing of major satellite transcripts in the maternal genome of the mouse embryo

Abstract: A striking proportion of human cleavage-stage embryos exhibit chromosome instability (CIN). Notably, until now, no experimental model has been described to determine the origin and mechanisms of complex chromosomal rearrangements. Here, we examined mouse embryos deficient for the chromatin remodeling protein ATRX to determine the cellular mechanisms activated in response to CIN. We demonstrate that ATRX is required for silencing of major satellite transcripts in the maternal genome, where it confers epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 69 publications
(106 reference statements)
2
62
0
Order By: Relevance
“…In U2OS cells, ATRX is deleted and telomere is maintained via the alternative lengthening of telomeres (ALT) pathway (30). It has been recently shown that C-SCE is enhanced in mouse embryos lacking ATRX, and suggested that this hyperrecombination may result in chromosome breakage at the centromere and fusion (25). Thus, it is likely that multiple mechanisms drive centromere instability in cancer cells.…”
Section: Cenp-a-dependent Mechanism To Maintain Centromere Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…In U2OS cells, ATRX is deleted and telomere is maintained via the alternative lengthening of telomeres (ALT) pathway (30). It has been recently shown that C-SCE is enhanced in mouse embryos lacking ATRX, and suggested that this hyperrecombination may result in chromosome breakage at the centromere and fusion (25). Thus, it is likely that multiple mechanisms drive centromere instability in cancer cells.…”
Section: Cenp-a-dependent Mechanism To Maintain Centromere Integritymentioning
confidence: 99%
“…Suppression of meiotic recombination at centromeres is established in eukaryotes, including human (19,21), whereas active mitotic recombination at the centromere has been reported in budding yeast, fission yeast, and mice (22)(23)(24)(25). In mice, DNA methylation by the DNA methyltransferases DNMT3a/b and chromatin remodeler α-thalassemia mental retardation X-linked protein (ATRX) contruibutes to suppression of centromereassociated sister chromatid exchanges (C-SCEs) (24,25), but it remains unclear whether human centromeres actively undergo recombination, and whether a direct mechanism exists to suppress illegitimate recombination within the core centromeric HOR.…”
mentioning
confidence: 99%
“…It is known that either incorporation of mutant H3.3 or interference with expression of reverse major satellite RNAs affects CF and blocks development at the 2-cell stage (Santenard et al 2010;Casanova et al, 2013). Notably, DAXX also fails to be incorporated into constitutive heterochromatin at PNBs in ATRX-deficient zygotes (De La Fuente et al 2015) indicating that ATRX and DAXX act as a complex during CF, as they do at heterochromatic regions in other cell types (Voon et al 2015).…”
Section: Specification Of Imprints In the Mouse Occurs Around The Timmentioning
confidence: 99%
“…Having an experimental method to induce mixing of the parental genomes in the zygote, put us in a position to test the hypothesis that nuclear compartmentalization plays a role in resolving epigenetic asymmetry in early development as proposed previously (Mayer, Smith et al 2000, Probst and Almouzni 2008, Duffie and Bourc'his 2013, De La Fuente, Baumann et al 2015.…”
mentioning
confidence: 99%